Breadth and Dynamics of Human Norovirus-Specific Antibodies in the First Year of Life. Issue 10 (18th July 2022) - Vielot, Nadja A; Brinkman, Amanda; DeMaso, Christina; Vilchez, Samuel; Lindesmith, Lisa C; Bucardo, Filemon; Reyes, Yaoska; Baric, Ralph S; Ryan, Elizabeth P; Braun, Ralph; Becker-Dreps, Sylvia
Abstract: We measured antibody binding to diverse norovirus virus-like particles over 12 months in 16 children. All had maternal antibodies at 2 months, with estimated lowest levels at 5 months of age. Antibody increases after 3 months suggested natural infections. This information could guide the timing of future norovirus vaccines. Abstract : Infants are born with IgG antibodies to multiple norovirus genotypes; waning immunity appears consistent with infection risk. Pediatric norovirus vaccines should be administered when titers are low enough to avoid interference from maternally acquired antibodies, but before antibodies have completely waned.